Occupational accident fatalities in Brazil: A time series study from 2011 to 2021. - Ramon Evangelista Dos Anjos Paiva; Thiffany Nayara Bento de Morais; Ketyllem Tayanne da Silva Costa; Renan Cipriano Moioli; Angelo Giuseppe Roncalli da Costa Oliveira; Fábia Barbosa de Andrade (PLoS ONE)
In Brazil, accidents at work generate temporary or permanent disability or death, with 2,556 deaths in 2021. The objective of this work is to evaluate the lethality rate due to formal work accidents in relation to the Brazilian regions, in the historical series of 2011 and 2021. An ecological time series analysis using secondary data from reports of accidents at work available from the National Institute of Social Security. To calculate the lethality rates, we used occupational accidents and mortality by region in Brazil. Brazil presented a rate of 61 deaths for every 100,000 formal work accidents in 2011, the country presents a downward curve to 32 deaths for 100,000 work accidents in 2011, being a decrease of 52% in relation to the beginning. The world panel shows how much Brazil is part of a scenario seen around the planet, with 318,000 deaths due to accidents and 2 million due to work-related diseases. Accidents at work account for 18% of deaths in low- and middle-income countries such as Brazil, compared to only 5% in high-income countries. This study revealed the need to strengthen public policies such as the National Workers' Health Policy, including the strengthening of Renast or even a more robust intersectoral approach.